Activity scheduling for Cost-Time investment optimization in project management (2008)
The Cost-Time Profile is a tool that presents the combined impact of disbursements made during the execution of a project, and their timing. The Cost-Time Profile chart presents the accumulated cost at any given time, and the area under the curve is the Cost-Time Investment. This Cost-Time Investment has a quantifiable impact on the working capital the company uses, and it is also useful for the determination of the Direct Cost of a product. This paper aims to develop a model to create the schedule of activities that minimizes the Cost-Time Investment for a project.